PENGARUH BEBAN KERJA, DUKUNGAN SOSIAL DAN KESEJAHTERAAN PSIKOLOGIS TERHADAP QUALITY OF WORK LIFE GURU SMK DI KECAMATAN PANONGAN KABUPATEN TANGERANG - Vina Riani; Ersam Mahendrawan; Surasni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the relationships between workload, social support, and psychological well-being and teachers' Quality of Work Life (QWL), both partially and simultaneously, among vocational high school (SMK) teachers in Panongan District, Tangerang Regency. This study employed a quantitative approach using a survey method with a correlational research design. The study population consisted of 164 teachers, from which 116 respondents were selected using the Slovin formula with a 5% margin of error and a proportional random sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using simple and multiple linear regression with IBM SPSS Statistics. The findings revealed that workload had a negative and significant relationship with teachers' Quality of Work Life (β = -0.572; r = -0.722; R² = 0.521; p < 0.001). Social support showed a positive and significant relationship with teachers' Quality of Work Life (β = 0.608; r = 0.745; R² = 0.555; p < 0.001). Psychological well-being also demonstrated a positive and significant relationship with teachers' Quality of Work Life (β = 0.584; r = 0.712; R² = 0.507; p < 0.001). Simultaneously, workload, social support, and psychological well-being exhibited a very strong and significant relationship with teachers' Quality of Work Life, with a multiple correlation coefficient of 0.852, a coefficient of determination of 0.726, and an F-value of 98.824 (p < 0.001). These findings indicate that improving social support and psychological well-being, while maintaining a manageable workload, plays a crucial role in enhancing teachers' Quality of Work Life.